(untitled) (Medicine Today, 2026)
Introduction: Self-medication is a common public health problem in Bangladesh, influenced by the easy availability of medicines and limited regulatory enforcement. Irrational drug use, especially antibiotics, poses serious health risks. Objective: To determine the prevalence of self-medication and identify associated factors among the general population of Bangladesh. Materials and Methods: A descriptive cross-sectional study was conducted from June to August 2025 among 450 adults in selected urban and rural areas. Data were collected using a structured questionnaire. Descriptive statistics and chi-square tests were performed using SPSS (v26), with a significance level of p < 0.05. Results: The prevalence of self-medication was 67.8%. Frequently used medicines included analgesics (48.3%), antibiotics (26.4%), antihistamines (22.7%) and gastrointestinal agents (18.2%). Major reasons for self-medication were previous experience with similar illness (42.1%), saving time (27.3%), and avoiding consultation fees (18.9%). Significant associations were found between self-medication and education level (p=0.031), monthly income (p=0.017), and easy access to drug stores (p=0.009). Conclusion: Self-medication is widely prevalent, with considerable misuse of antibiotics. Public health education, pharmacist-led counseling, and stronger regulatory measures are necessary to minimize inappropriate self-medication practices. Medicine Today 2026, Vol.38 (1): 133-136